Adverse Maternal Outcomes Differ between Obese and Nonobese Women with Severe Preeclampsia - Teefey, Christina Paidas; Durnwald, Celeste P.; Srinivas, Sindhu K.; Levine, Lisa D. (American Journal of Perinatology, 2019)
Objective This article evaluates the differences in adverse maternal outcomes related to severe preeclampsia in obese versus nonobese women.Study Design Retrospective cohort study and planned secondary analysis of women with severe preeclampsia comparing a composite adverse maternal outcome related to preeclampsia among obese (body mass index [BMI] ≥ 30 kg/m2) and nonobese (BMI < 30 kg/m2) women. The composite outcome was defined as ≥ 1 of the following prior to discharge: renal failure, liver abnormality, thrombocytopenia, blood transfusion, pulmonary edema, disseminated intravascular coagulation, stroke, or eclampsia. Multivariable logistic regression was used to control for confounders.Results Of the 152 women included, 37.5% were obese and 62.5% were nonobese. The prevalence of the primary outcome was 15.8% with obese women less likely to have the composite outcome compared with nonobese women (7% vs. 21.1%, p = 0.02). This remained after adjusting for confounders including maternal age, race, and chronic hypertension (adjusted odds ratio, 0.33 [0.12–0.89], p = 0.03). Obese women were, however, more likely to require intravenous antihypertensive medication peripartum compared with nonobese women (49.1% vs. 28.4%, p = 0.01).Conclusion Obese women with severe preeclampsia may have a different phenotype of severe preeclampsia that is more associated with severe hypertension rather than end-organ damage.
Keywords: obesity; severe preeclampsia; preeclampsia with severe features; adverse maternal outcome; phenotype